Assessing the economic profitability of fodder legume production for Green Biorefineries – A cost-benefit analysis to evaluate farmers profitability. (20th January 2016) - Papendiek, Franka; Tartiu, Valentina E.; Morone, Piergiuseppe; Venus, Joachim; Hönig, Anne
Abstract: Fodder legumes play a major role in developing sustainable agricultural production systems and contain a range of compounds, which can be utilized to produce a wide spectrum of materials currently manufactured from petroleum-based sources. Hence, if associated with Green Biorefinery technology, the use of fodder legumes brings about significant advantages in terms of overall environmental sustainability. Since fodder legume production in Europe is currently very low, the objective of this study is to assess if a new value chain generated by Green Biorefineries can make fodder legume production profitable for farmers, and therewith increase cultivation numbers. We conducted a financial cost-benefit analysis of producing biomass from agricultural land in the federal state of Brandenburg (Germany) in three different production scenarios at two farm size levels. Costs, benefits, expected profits and risks between the scenarios were quantified. Fodder legume production for traditional fodder production was already able to increase the internal rate of return, while the production of feedstocks for Green Biorefineries, depending on prices paid for the legume juice showed an even higher profit potential. Therefore, in future agricultural production systems, fodder legumes should be part of crop rotations again. Highlights: Fodder legumes associated with Green Biorefineries can produce several materials. These can substitute those currently manufactured from petroleum-based sources. A financial cost-benefit analysis was conducted in the state of Brandenburg, Germany. We considered three different production scenarios at two farm size levels. Green Biorefineries can make fodder legume production profitable for farmers.